2019
DOI: 10.3390/su11133530
|View full text |Cite
|
Sign up to set email alerts
|

Projection of Long-Term Care Costs in China, 2020–2050: Based on the Bayesian Quantile Regression Method

Abstract: The aging population in China highlights the significance of elderly long-term care (LTC) services. The number of people aged 65 and above increased from 96 million in 2003 to 150 million in 2016, some of whom were disabled due to chronic diseases or the natural effects of aging on bodily functions. Therefore, the measurement of future LTC costs is of crucial value. Following the basic framework but using different empirical methods from those presented in previous literature, this paper attempts to use the Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 24 publications
2
43
0
1
Order By: Relevance
“…Similar to the prediction results in previous studies [21], the predicted results in this study showed that the number of disabled elderly will increase in both urban and rural areas, and community home-based care will continue to be the mainstream type of LTC. Previous research has shown that community home-based care is more popular with the elderly than institutional care [47].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to the prediction results in previous studies [21], the predicted results in this study showed that the number of disabled elderly will increase in both urban and rural areas, and community home-based care will continue to be the mainstream type of LTC. Previous research has shown that community home-based care is more popular with the elderly than institutional care [47].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, any information on how much will be needed to pay for LTCI is crucial for Chinese policy makers attempting to design a sustainable LTCI financing policy. As such, the measurement of LTC costs is one of the most important research topics, both today and in the future [21].…”
Section: Ltci In China and Other Countriesmentioning
confidence: 99%
“…LTC demands in underdeveloped countries, including China, are growing at a rate much faster than that in developed countries. 2 In recent years, China has to bear the long-term labor demand pressure brought by the aging of the population. China has the largest number of elderly people in the world (over 60 years old).…”
Section: Introductionmentioning
confidence: 99%
“…From an economic point of view, if the glass collected from the La Liga Peque Recicladores program were sold on the market, the income generated could lead to self-financing of this educational activity; similar paper recycling education programs have already adopted this method of self-funding [29]. Furthermore, this glass recycling program is not only capable of generating income, but it could also lead to economic savings in the high healthcare and environmental costs resulting from pollution [63][64][65][66][67][68][69][70][71][72][73]. Therefore, governments should pay attention to the link between health and the environment when formulating public policies; likewise, it is incumbent upon the private industry to develop socially responsible behaviors.…”
Section: Discussionmentioning
confidence: 99%